Ultraviolet curing flame-retardant coating for new energy cell coating and preparation method of ultraviolet curing flame-retardant coating

By using ultraviolet curing flame retardant coatings with modified epoxy acrylate and acrylic resin on new energy battery cells, the problem of insufficient adhesion of traditional coatings on metal substrates is solved, and good flame retardant performance, adhesion, thermal stability and stiffness are achieved.

CN119823350APending Publication Date: 2025-04-15JIANGXI JINSHI 3D AM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311330002.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing ultraviolet curing coatings have poor adhesion on metal substrates and it is difficult to maintain low shrinkage and certain stiffness while ensuring metal adhesion.

Method used

By reacting acid anhydride, organic solvent and flame retardant, modified epoxy acrylic acid ester is prepared, combined with the reaction of epoxy resin and acrylic acid to form an ultraviolet-cured flame retardant acrylic resin with excellent rigidity, mechanical properties and thermal stability, and an adhesion accelerator is added to improve the adhesion of the metal substrate.

Benefits of technology

UV cured coatings with good flame retardant properties, metal adhesion properties, thermal stability properties and certain stiffness on new energy battery cells have been achieved, solving the problem of insufficient adhesion of traditional coatings on metal substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004493890790000091
    Figure BDA0004493890790000091
Patent Text Reader

Abstract

The invention discloses an ultraviolet-curing flame-retardant coating for a new energy cell coating and a preparation method of the ultraviolet-curing flame-retardant coating. According to the preparation method of ultraviolet-curing flame-retardant epoxy acrylate, the ultraviolet-curing flame-retardant epoxy acrylate is prepared from raw materials including anhydride, a flame retardant, an organic solvent I, epoxy resin, acrylic acid, an organic solvent II, a polymerization inhibitor and a catalyst according to a certain proportion. The invention also discloses an ultraviolet curing coating which comprises 10-30 parts of the ultraviolet curing phosphorus-nitrogen flame-retardant acrylic resin, 70-90 parts of acrylate resin, 10-30 parts of a reactive diluent, 1-5 parts of a photoinitiator and 1-5 parts of an adhesion promoter. The ultraviolet curing coating for a new energy battery cell coating prepared from the ultraviolet curing coating has relatively high metal adhesive force, and also has good flame retardance, thermal stability and certain rigidity at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical coating processing, and in particular to an ultraviolet light-cured flame-retardant coating for new energy battery core coating and a preparation method thereof. Background Art

[0002] At present, new energy battery cells are mainly coated with blue film, which is an insulating material to isolate each battery cell. However, the blue film is prone to defects such as damage, bulges and bubbles, which can easily affect the performance of the battery cell. With the rapid growth of demand and consumption of new energy batteries, powder coatings gradually replace blue films for use in high-end battery cells, which has a very broad prospect.

[0003] UV curing coating systems are generally composed of oligomers, reactive diluents, photoinitiators and other additives. Compared with traditional thermal curing coatings, UV curing coatings have the advantages of fast curing speed, energy saving and environmental protection, and have been widely used in many fields such as wooden furniture, optical fiber coatings, food packaging, magazine covers, etc. However, UV curing coatings are rarely used on metal substrates, especially aluminum, so it is very necessary to develop light-curing coatings suitable for new energy batteries.

[0004] On the one hand, the flame retardants currently used to modify UV-curable coatings can be roughly divided into halogen flame retardants and halogen-free flame retardants based on elements. Halogen flame retardants mainly include chlorine-containing, bromine-containing flame retardants and their derivatives. The advantages of this flame retardant are stable performance, low price and easy processing. Halogen flame retardants will release toxic and harmful substances such as dioxins during the combustion reaction, causing secondary damage; halogen-free flame retardants include phosphorus-nitrogen flame retardants, intumescent flame retardants, graphene flame retardants and silicone flame retardants. Phosphorus-nitrogen flame retardants are currently the most widely used environmentally friendly flame retardants, among which phosphorus-based flame retardants can generate a relatively stable carbon layer during the combustion process to prevent heat transfer, thereby achieving a flame retardant effect.

[0005] On the other hand, the main reason why UV coatings have poor adhesion on metal substrates is due to the high density of the metal surface. The hydrogen bonds or chemical bonds formed between the oligomers and the metal surface are not enough to meet the adhesion requirements. At the same time, UV light-curing coatings have a fast curing speed and volume shrinkage, which produces great internal stress, which reacts on the adhesion of the coating. Therefore, on the basis of ensuring a certain adhesion to the metal substrate, it is also necessary to ensure that the coating has a low shrinkage rate and a certain rigidity.

[0006] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a UV-curable flame-retardant coating for new energy batteries and a preparation method thereof, which has the advantages of good flame retardancy, good metal adhesion, good thermal stability and certain rigidity.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing ultraviolet light-cured flame-retardant coating for new energy battery cells:

[0009] (1) mixing an acid anhydride, a flame retardant and an organic solvent I, reacting at 40 to 70° C. for 4 to 10 hours, and obtaining an acid anhydride intermediate through recrystallization and vacuum drying;

[0010] Preferably, the acid anhydride is one or more of maleic anhydride, itaconic anhydride or citraconic anhydride.

[0011] Preferably, the flame retardant is one or more of N,N-bis(2-hydroxyethyl)aminomethylene diethyl phosphate (FRC6), dimethyl phosphite, diethyl phosphite, bis(4-hydroxyphenyl)phenyl phosphine oxide or 2,2-bis(bromomethyl)1,3-propylene glycol.

[0012] More preferably, the molar ratio of the acid anhydride to the flame retardant is 2:1 to 1:2; and the amount of the organic solvent I used is to ensure that the concentration of the acid anhydride and the flame retardant is 0.5 to 1.5 g / mL.

[0013] (2) mixing the acid anhydride intermediate, acrylic acid, organic solvent II, a polymerization inhibitor and a catalyst, reacting at 80 to 130° C. for 4 to 10 hours, and then precipitating with deionized water and vacuum drying to obtain an acrylic acid intermediate;

[0014] Preferably, the organic solvent I is one or more of hexanediol, octanediol or decanediol.

[0015] Preferably, the organic solvent II is one or more of 1,4-dioxane, N,N-dimethylformamide, toluene, dimethyl sulfoxide, N,N-dimethylacetamide, and N-methyl-pyrrolidone.

[0016] More preferably, the molar ratio of the phosphoric acid anhydride intermediate to acrylic acid is 2:1 to 1:2; the amount of the organic solvent II is to ensure that the concentration of the phosphoric acid anhydride intermediate and acrylic acid is 0.5 to 1.5 g / mL.

[0017] (3) mixing an acrylic intermediate, an epoxy resin, an organic solvent II, an inhibitor and a catalyst, reacting the mixture at 80 to 120° C. for 4 to 10 hours, and then precipitating the mixture with deionized water and vacuum drying the mixture to obtain an ultraviolet light-cured flame-retardant acrylic resin;

[0018] Preferably, the epoxy resin is epoxy resin E51.

[0019] Preferably, the polymerization inhibitor is one or more of hydroquinone or p-methoxyphenol.

[0020] Preferably, the catalyst is one or more of tetraethylammonium bromide, triphenylphosphine, p-toluenesulfonic acid or N,N'-dimethylbenzylamine;

[0021] More preferably, the molar ratio of the acrylic acid intermediate to the epoxy resin is 1 to 4:1; the amount of the organic solvent II is to ensure that the concentration of the acrylic acid intermediate and the epoxy resin is 0.05 to 0.8 g / mL.

[0022] Further preferably, in step (2), the amount of the polymerization inhibitor is 0.05-0.5% of the total mass of the anhydride intermediate and the acrylic acid; the amount of the catalyst is 0.05-5% of the total mass of the anhydride intermediate and the acrylic acid; further preferably, in step (3), the amount of the polymerization inhibitor is 0.05-0.5% of the total mass of the acrylic acid intermediate and the nitrogen-containing epoxy resin; the amount of the catalyst I is 0.5-5% of the total mass of the phosphorus-containing acrylic acid intermediate and the nitrogen-containing epoxy resin.

[0023] A UV-curable flame-retardant coating for new energy batteries, comprising 10 to 30 parts of the UV-curable phosphorus-nitrogen flame-retardant acrylic resin, 70 to 90 parts of acrylate resin, 10 to 30 parts of active diluent, 1 to 5 parts of photoinitiator, and 1 to 5 parts of adhesion promoter.

[0024] Preferably, the reactive diluent is one or more of hydroxyethyl methacrylate (HEMA), 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), and trimethylolpropane triacrylate (TMPTA).

[0025] Preferably, the photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone (Irgacure-184), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (Lucirin TPO), and 2-hydroxy-2-methyl-1-phenyl-1-propanone (Darocur 1173).

[0026] Preferably, the adhesion promoter is one or more of acrylated phosphate, KH550, tetraisooctyl titanate, tetraisopropyl titanate, and n-butyl titanate.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] The present invention reacts anhydride, organic solvent and flame retardant, wherein the flame retardant adopts phosphorus nitrogen flame retardant and is not easy to generate harmful gas, and then undergoes ring-opening reaction with epoxy resin, and is capped with acrylic acid to prepare modified epoxy acrylate for UV curable coating. The prepared modified epoxy acrylate has excellent rigidity, mechanical properties and thermal stability. The multifunctional unsaturated double bonds can participate in the photocuring reaction, increase the crosslinking density of the coating, and thus increase the hardness of the coating. The added adhesion promoter can improve the adhesion to the metal substrate. DETAILED DESCRIPTION

[0029] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0030] Example 1

[0031] (1) Preparation of anhydride intermediates

[0032] 25.67g FRC-6 and 10.11g maleic anhydride were dissolved in 35.46mL hexanediol, added into a 100mL single-necked flask, and reacted at 650°C for 6h. After the reaction was completed, recrystallization was performed, and then washed with a large amount of anhydrous ethanol for several times, and vacuum dried at 60°C for 24h to obtain a pure white solid product, i.e., the acid anhydride intermediate.

[0033] (2) Preparation of acrylic acid intermediates

[0034] 35.63 g of anhydride intermediate, 3 wt % of catalyst tetraethylammonium bromide and 0.1 wt % of inhibitor hydroquinone were first dissolved in 82 mL of 1,4-dioxane, and then 13.65 g of acrylic acid was quickly added, and the temperature was raised to 110° C. During the reaction, the acid value change in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the system was cooled to room temperature. After rotary evaporation and concentration, the system was precipitated and washed several times in hot water at 85° C. and ether, and vacuum dried at 45° C. for 12 hours to obtain a transparent oily liquid, i.e., the acrylic acid intermediate.

[0035] (3) Preparation of UV-curable flame-retardant acrylic resin

[0036] 92.46 g of acrylic acid intermediate, 25.63 g of epoxy resin E51, 4 wt % of catalyst tetraethylammonium bromide, 384 mL of 1,4-dioxane and 0.1 wt % of inhibitor hydroquinone were added into a flask, and the reaction was carried out at 120° C. During the reaction, the change of acid value in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the mixture was cooled to room temperature. After the solvent was removed by rotary evaporation, a UV-curable flame-retardant acrylic resin was obtained.

[0037] Example 2

[0038] A UV-curable coating containing UV-curable flame-retardant acrylic resin, wherein the preparation method of the UV-curable coating is as follows:

[0039] 30 parts of the UV-curable flame-retardant acrylic resin obtained in Example 1, 70 parts of epoxy acrylic resin and 30 parts of active diluent HEMA were stirred into a homogeneous phase at room temperature, and then 3 parts of photoinitiator 184, 0.5 parts of adhesion promoter acrylated phosphate, 0.5 parts of defoamer and 0.5 parts of leveling agent were added, and stirring was continued for 10 minutes at a speed of 1500 r / min in the dark to obtain a UV-curable coating of flame-retardant resin.

[0040] Example 3

[0041] (1) Preparation of anhydride intermediates

[0042] 25.67 g of dimethyl phosphite and 12.57 g of itaconic anhydride were dissolved in 36.75 mL of octanediol, added to a 100 mL single-necked flask, and reacted at 60° C. for 6 h. After the reaction was completed, recrystallization was performed, and then washed several times with a large amount of anhydrous ethanol, and vacuum dried at 55° C. for 24 h to obtain a pure white solid product, i.e., the anhydride intermediate.

[0043] (2) Preparation of acrylic acid intermediates

[0044] 36.43 g of anhydride intermediate, 3 wt % of catalyst triphenylphosphine and 0.1 wt % of inhibitor hydroquinone were first dissolved in 108.75 mL of N,N-dimethylformamide, and then 13.65 g of acrylic acid was quickly added, and the temperature was raised to 120° C. During the reaction, the acid value change in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the system was cooled to room temperature. After rotary evaporation and concentration, the system was precipitated and washed several times in hot water at 90° C. and ether, and vacuum dried at 45° C. for 12 hours to obtain a transparent oily liquid, i.e., the acrylic acid intermediate.

[0045] (3) Preparation of UV-curable flame-retardant acrylic resin

[0046] 108.75 g of acrylic acid intermediate, 27.93 g of epoxy resin E51, 4 wt % of catalyst triphenylphosphine, 465.73 mL of N, N-dimethylformamide and 0.1 wt % of inhibitor hydroquinone were added into a flask, and the reaction was carried out at 110° C. During the reaction, the change of acid value in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the mixture was cooled to room temperature. After the solvent was removed by rotary evaporation, a UV-curable flame-retardant acrylic resin was obtained.

[0047] Example 4

[0048] A photocurable coating containing a UV-curable flame-retardant acrylic resin. The preparation method of the photocurable coating comprises the following steps: stirring 30 parts of the UV-curable flame-retardant acrylic resin obtained in Example 3, 70 parts of epoxy acrylic resin and 30 parts of active diluent HDDA into a homogeneous phase at room temperature, then adding 3 parts of photoinitiator TPO, 0.5 parts of adhesion promoter KH550, 0.5 parts of defoamer and 0.5 parts of leveling agent, and continuing stirring at a speed of 1500 r / min in the dark for 10 minutes to obtain a UV-curable coating of the flame-retardant resin.

[0049] Example 5

[0050] (1) Preparation of anhydride intermediates

[0051] 28.47 g of diethyl phosphite and 14.23 g of maleic anhydride were dissolved in 64.37 mL of decanediol, added to a 100 mL single-necked flask, and reacted at 60° C. for 8 h. After the reaction was completed, recrystallization was performed, and then washed with a large amount of anhydrous ethanol for several times, and vacuum dried at 50° C. for 20 h to obtain a pure white solid product, i.e., the acid anhydride intermediate.

[0052] (2) Preparation of acrylic acid intermediates

[0053] 43.57g of anhydride intermediate, 3wt% of catalyst p-toluenesulfonic acid and 0.1wt% of inhibitor hydroquinone were first dissolved in 93mL of toluene, and then 13.65g of acrylic acid was quickly added, and the temperature was raised to 110°C. During the reaction, the acid value change in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the system was cooled to room temperature. After rotary evaporation and concentration, the system was precipitated and washed several times in hot water at 85°C and ether, and vacuum dried at 45°C for 12h to obtain a transparent oily liquid, i.e., the acrylic acid intermediate.

[0054] (3) Preparation of UV-curable flame-retardant acrylic resin

[0055] 92.46 g of acrylic acid intermediate, 23.67 g of epoxy resin E51, 4 wt % of catalyst p-toluenesulfonic acid, 413 mL of toluene and 0.1 wt % of inhibitor hydroquinone were added into a flask and reacted at 110° C. During the reaction, the acid value change in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and cooled to room temperature. After the solvent was removed by rotary evaporation, a UV-curable flame-retardant acrylic resin was obtained.

[0056] Example 6

[0057] A UV-curable coating containing UV-curable flame-retardant acrylic resin, wherein the preparation method of the UV-curable coating is as follows:

[0058] 30 parts of the photocurable flame-retardant acrylic resin obtained in Example 1, 70 parts of epoxy acrylic resin and 30 parts of active diluent TPGDA were stirred into a homogeneous phase at room temperature, and then 3 parts of photoinitiator 1173, 0.5 parts of adhesion promoter tetraethyl hexyl titanate, 0.5 parts of defoamer and 0.5 parts of leveling agent were added, and stirring was continued for 10 minutes at a speed of 1500 r / min in the dark to obtain a flame-retardant resin UV-curable coating.

[0059] Example 7

[0060] (1) Preparation of anhydride intermediates

[0061] 23.93 g of bis(4-hydroxyphenyl)phenylphosphine oxide and 12.34 g of citraconic anhydride were dissolved in 35.47 mL of octanediol, added to a 100 mL single-necked flask, and reacted at 50° C. for 5 h. After the reaction was completed, recrystallization was performed, and then washed several times with a large amount of anhydrous ethanol, and vacuum dried at 50° C. for 24 h to obtain a pure white solid product, i.e., the anhydride intermediate.

[0062] (2) Preparation of acrylic acid intermediates

[0063] 40.17 g of anhydride intermediate, 3 wt % of catalyst N,N'-dimethylbenzylamine and 0.05 wt % of inhibitor p-methoxyphenol were first dissolved in 85 mL of dimethyl sulfoxide, and then 24.65 g of acrylic acid was quickly added, and the temperature was raised to 110° C. During the reaction, the acid value change in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the system was cooled to room temperature. After rotary evaporation and concentration, the system was precipitated and washed several times in hot water at 85° C. and ether, and vacuum dried at 45° C. for 12 hours to obtain a transparent oily liquid, i.e., the acrylic acid intermediate.

[0064] (3) Preparation of UV-curable flame-retardant acrylic resin

[0065] 184.46 g of acrylic acid intermediate, 27.54 g of epoxy resin E51, 4 wt % of catalyst N, N'-dimethylbenzylamine, 425 mL of dimethyl sulfoxide and 0.2 wt % of inhibitor p-methoxyphenol were added into a flask, and the reaction was carried out at 110° C. During the reaction, the change of acid value in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the mixture was cooled to room temperature. After the solvent was removed by rotary evaporation, a UV-curable flame-retardant acrylic resin was obtained.

[0066] Example 8

[0067] A UV-curable coating containing UV-curable flame-retardant acrylic resin. The preparation method of the UV-curable coating is as follows: 30 parts of the UV-curable flame-retardant acrylic resin obtained in Example 1, 70 parts of epoxy acrylic resin and 30 parts of active diluent TMPTA are stirred into a homogeneous phase at room temperature, and then 3 parts of photoinitiator 184, 0.5 parts of adhesion promoter tetraisopropyl titanate, 0.5 parts of defoamer and 0.5 parts of leveling agent are added, and stirring is continued for 10 minutes at a speed of 1500 r / min in the dark to obtain the UV-curable coating of the flame-retardant resin.

[0068] Example 9

[0069] (1) Preparation of anhydride intermediates

[0070] 18.45g of 2,2-bis(bromomethyl)-1,3-propanediol and 11.24g of itaconic anhydride were dissolved in 45.37mL of hexanediol, added into a 100mL single-necked flask, and reacted at 70°C for 6h. After the reaction was completed, recrystallization was performed, and then washed several times with a large amount of anhydrous ethanol, and vacuum dried at 50°C for 24h to obtain a pure white solid product, i.e., the anhydride intermediate.

[0071] (2) Preparation of acrylic acid intermediates

[0072] 23.56g of anhydride intermediate, 3wt% of catalyst tetraethylammonium bromide and 0.05wt% of inhibitor hydroquinone were first dissolved in 53.56mL of N,N-dimethylacetamide, and then 26.35g of acrylic acid was quickly added, and the temperature was raised to 110°C. During the reaction, the acid value change in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the system was cooled to room temperature. After rotary evaporation and concentration, the system was precipitated and washed several times in hot water at 90°C and ether, and vacuum dried at 45°C for 12h to obtain a transparent oily liquid, i.e., the acrylic acid intermediate.

[0073] (3) Preparation of UV-curable flame-retardant acrylic resin

[0074] 207.43 g of acrylic acid intermediate, 34.64 g of epoxy resin E51, 3 wt % of catalyst tetraethylammonium bromide, 495 mL of N,N-dimethylacetamide and 0.2 wt % of inhibitor hydroquinone were added into a flask, and the reaction was carried out at 100° C. During the reaction, the change of acid value in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the mixture was cooled to room temperature. After the solvent was removed by rotary evaporation, a UV-curable flame-retardant acrylic resin was obtained.

[0075] Example 10

[0076] A UV-curable coating containing UV-curable flame-retardant acrylic resin. The preparation method of the UV-curable coating is as follows: 30 parts of the UV-curable flame-retardant acrylic resin obtained in Example 9, 70 parts of epoxy acrylic resin and 30 parts of active diluent HEMA are stirred into a homogeneous phase at room temperature, and then 3 parts of photoinitiator TPO, 0.5 parts of adhesion promoter n-butyl titanate, 0.5 parts of defoamer, and 0.5 parts of leveling agent are added, and stirring is continued for 10 minutes at a speed of 1500 r / min in the dark to obtain a UV-curable coating of flame-retardant resin.

[0077] Embodiment 11

[0078] (1) Preparation of anhydride intermediates

[0079] 20.32g FRC-6 and 9.65g maleic anhydride were dissolved in 38.43mL octanediol, added into a 100mL single-necked flask, and reacted at 60°C for 8h. After the reaction was completed, recrystallization was performed, and then washed with a large amount of anhydrous ethanol for several times, and vacuum dried at 50°C for 24h to obtain a pure white solid product, i.e., the acid anhydride intermediate.

[0080] (2) Preparation of acrylic acid intermediates

[0081] 23.56g of anhydride intermediate, 2wt% of catalyst triphenylphosphine and 0.1wt% of inhibitor p-methoxyphenol were first dissolved in 53.56mL of N-methyl-pyrrolidone, and then 26.35g of acrylic acid was quickly added, and the temperature was raised to 110°C. During the reaction, the acid value change in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the system was cooled to room temperature. After rotary evaporation and concentration, the system was precipitated and washed several times in hot water at 90°C and ether, and vacuum dried at 45°C for 12h to obtain a transparent oily liquid, i.e., the acrylic acid intermediate.

[0082] (3) Preparation of UV-curable flame-retardant acrylic resin

[0083] 232.45 g of acrylic acid intermediate, 41.64 g of epoxy resin E51, 3 wt % of catalyst triphenylphosphine, 625.32 mL of N-methyl-pyrrolidone and 0.2 wt % of inhibitor p-methoxyphenol were added into a flask, and the reaction was carried out at 100° C. During the reaction, the change of acid value in the system was monitored in real time. When the acid value remained unchanged, the reaction was stopped and the mixture was cooled to room temperature. After the solvent was removed by rotary evaporation, a UV-curable flame-retardant acrylic resin was obtained.

[0084] Example 12

[0085] A UV-curable coating containing UV-curable flame-retardant acrylic resin, wherein the preparation method of the UV-curable coating is as follows:

[0086] 30 parts of the UV-curable flame-retardant acrylic resin obtained in Example 9, 70 parts of epoxy acrylic resin and 30 parts of active diluent HDDA were stirred into a homogeneous phase at room temperature, and then 3 parts of photoinitiator 1173, 0.5 parts of adhesion promoter acrylated phosphate, 0.5 parts of defoamer and 0.5 parts of leveling agent were added, and stirring was continued for 10 minutes at a speed of 1500 r / min in the dark to obtain a UV-curable coating of flame-retardant resin.

[0087] Comparative Example 1

[0088] The difference from Example 1 is that the comparative example 1 does not add the UV-curable flame-retardant acrylic resin synthesized in Example 1.

[0089] Comparative Example 2

[0090] The difference from Example 3 is that the comparative example 2 does not add the UV-curable flame-retardant acrylic resin synthesized in Example 3.

[0091] Comparative Example 3

[0092] The difference from Example 5 is that the comparative example 3 does not add the UV-curable flame-retardant acrylic resin synthesized in Example 5.

[0093] Comparative Example 4

[0094] The difference from Example 2 is that the adhesion promoter in Example 2 is not added in Comparative Example 4.

[0095] Comparative Example 5

[0096] The difference from Example 4 is that the adhesion promoter in Example 4 is not added in Comparative Example 5.

[0097] Comparative Example 6

[0098] The difference from Example 6 is that the adhesion promoter in Example 6 is not added in Comparative Example 6.

[0099] Coating performance test The coatings of Examples 2, 4, 6, 8, 10, 12 and Comparative Examples 1 to 6 were respectively coated on aluminum plates and cured under an ultraviolet light curing machine. The properties of the resulting coating films are shown in Table 1.

[0100] Table 1 Coating performance determination

[0101]

[0102] Note: Pencil hardness is measured according to GB / T6739-2006, adhesion is measured according to GB / T9286-1998, tensile properties are measured according to GB / T16421-1996, limiting oxygen index (LOI) is measured according to ASTMD2863-2017, vertical burning test (UL-94) is measured according to ASTMD3801-2010, / indicates that UL-94 does not reach the grade, and impact resistance is measured according to GB / T1732-1993.

[0103] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a UV-curable flame-retardant epoxy acrylate resin, characterized in that: The invention is prepared from raw materials including acid anhydride, flame retardant, organic solvent I, organic solvent II, epoxy resin, acrylic acid, polymerization inhibitor and catalyst.

2. The method for preparing the ultraviolet light-cured flame-retardant epoxy acrylate resin according to claim 1, characterized in that: The following steps are involved: (1) mixing an acid anhydride, a flame retardant and an organic solvent I, reacting at 40 to 70° C. for 4 to 10 hours, and obtaining an acid anhydride intermediate through recrystallization and vacuum drying; (2) mixing the acid anhydride intermediate, acrylic acid, organic solvent II, a polymerization inhibitor and a catalyst, reacting at 80 to 130° C. for 4 to 10 hours, and then precipitating with deionized water and vacuum drying to obtain an acrylic acid intermediate; (3) The acrylic intermediate, epoxy resin, organic solvent II, inhibitor and catalyst are mixed, reacted at 80-120° C. for 4-10 hours, and then precipitated with deionized water and vacuum dried to obtain a UV-curable flame-retardant acrylic resin.

3. The method for preparing the ultraviolet light-cured flame-retardant epoxy acrylic resin according to claim 2, characterized in that: The acid anhydride is one or more of maleic anhydride, itaconic anhydride or citraconic anhydride.

4. The method for preparing the ultraviolet light-cured flame-retardant epoxy acrylic resin according to claim 2, characterized in that: The flame retardant is one or more of N,N-bis(2-hydroxyethyl)aminomethylene diethyl phosphate (FRC6), dimethyl phosphite, diethyl phosphite, bis(4-hydroxyphenyl)phenyl phosphine oxide or 2,2-bis(bromomethyl)1,3-propylene glycol.

5. The method for preparing the ultraviolet light-cured flame-retardant epoxy acrylic resin according to claim 3, characterized in that: The molar ratio of the acid anhydride to the flame retardant monomer in step (1) is 2:1 to 1:2; the amount of the organic solvent I is to ensure that the concentration of the acid anhydride and the flame retardant monomer is 0.5 to 1.5 g / mL.

6. The method for preparing the ultraviolet light-cured flame-retardant epoxy acrylic resin according to claim 2, characterized in that: The organic solvent I is one or more of hexanediol, octanediol or decanediol.

7. The method for preparing the ultraviolet light-cured flame-retardant epoxy acrylic resin according to claim 2, characterized in that: The organic solvent II is one or more of 1,4-dioxane, N,N-dimethylformamide, toluene, dimethyl sulfoxide, N,N-dimethylacetamide, and N-methyl-pyrrolidone.

8. The method for preparing the ultraviolet light-cured flame-retardant epoxy acrylic resin according to claim 3, characterized in that: The molar ratio of the anhydride intermediate to the acrylic acid monomer in step (2) is 2:1 to 1:2; the amount of the organic solvent II used is to ensure that the concentration of the anhydride intermediate and the acrylic acid monomer is 0.5 to 1.5 g / mL.

9. The method for preparing the ultraviolet light-curable flame-retardant epoxy acrylic resin according to claim 2, characterized in that: The epoxy resin is epoxy resin E51.

10. The method for preparing the ultraviolet light-curable flame-retardant epoxy acrylic resin according to claim 2, characterized in that: The polymerization inhibitor is one or more of hydroquinone and p-methoxyphenol.

11. The method for preparing the ultraviolet light-curable flame-retardant epoxy acrylic resin according to claim 2, characterized in that: The catalyst is one or more of tetraethylammonium bromide, triphenylphosphine, p-toluenesulfonic acid or N,N'-dimethylbenzylamine.

12. The method for preparing the ultraviolet light-curable flame-retardant epoxy acrylic resin according to claim 3, characterized in that: The molar ratio of the acrylic acid intermediate to the epoxy resin in step (3) is 1 to 4:1; the amount of the organic solvent II used is to ensure that the concentration of the acrylic acid intermediate and the epoxy resin is 0.05 to 0.8 g / mL.

13. The method for preparing the ultraviolet light-curable flame-retardant epoxy acrylic resin according to claim 3, characterized in that: In step (2), the amount of the polymerization inhibitor is 0.05-0.5% of the total mass of the anhydride intermediate and acrylic acid; the amount of the catalyst is 0.05-5% of the total mass of the anhydride intermediate and acrylic acid.

14. The method for preparing the ultraviolet light-curable flame-retardant epoxy acrylic resin according to claim 3, characterized in that: In step (3), the amount of the polymerization inhibitor is 0.05-0.5% of the total mass of the acrylic acid intermediate and the epoxy resin; the amount of the catalyst I is 0.5-5% of the total mass of the acrylic acid intermediate and the epoxy resin.

15. A light-curing coating comprising the ultraviolet light-curing flame-retardant acrylic resin according to claim 1, characterized in that: The coating comprises 10 to 30 parts of the photocurable phosphorus-nitrogen flame-retardant acrylic resin, 70 to 90 parts of acrylate resin, 10 to 30 parts of reactive diluent, 1 to 5 parts of photoinitiator, and 1 to 5 parts of adhesion promoter.

16. The preparation method according to claim 15, characterized in that The active diluent is one or more of hydroxyethyl methacrylate (HEMA), 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), and trimethylolpropane triacrylate (TMPTA). Preferably, the photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone (Irgacure-184), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (Lucirin TPO), and 2-hydroxy-2-methyl-1-phenyl-1-propanone (Darocur 1173).

17. The preparation method according to claim 15, characterized in that The adhesion promoter is one or more of acrylated phosphate, KH550, tetraisooctyl titanate, tetraisopropyl titanate, and n-butyl titanate.